Evaluation of Avifauna Species Found in the Area of PT Arutmin Indonesia-NPLCT, Kota Baru, South Kalimantan - Mochamad Arief Soendjoto; Maulana Khalid Riefani; Muhammad Zen (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2015)
Avifauna is a biological aspect, which is easy to use as a decision making to arrange the development of the mining-product port area on postmining. The objective of the research was to evaluate composition of avifauna species in the area of PT Arutmin Indonesia – NPLCT based on the presence or the residence, the preference to the habitat type, the dominant diet, and the propagation indicator. Evaluation was conducted through grouping the field data or published databased on such four parameters and comparing to the references. Among 57 avifauna species in the area, 39 are resident, because they were always found in all observations. A single species is an endemic to Kalimantan. Five other species may be migrants originating relatively far from the research area. Avifauna was likely to prefer secondary forest to other habitat types. Based on dominant diet, there were frugivore, granivore, insectivore, carnivore, nectarivore, omnivore, and piscivore. Various nests were found and those reflected opportunity the birds to propagate in the areaKeywords: bird, diet, evaluation, habitat type, residence